2016
DOI: 10.1002/ece3.2650
|View full text |Cite
|
Sign up to set email alerts
|

Hopes and challenges for giant panda conservation under climate change in the Qinling Mountains of China

Abstract: One way that climate change will impact animal distributions is by altering habitat suitability and habitat fragmentation. Understanding the impacts of climate change on currently threatened species is of immediate importance because complex conservation planning will be required. Here, we mapped changes to the distribution, suitability, and fragmentation of giant panda habitat under climate change and quantified the direction and elevation of habitat shift and fragmentation patterns. These data were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The difference may be attributed to different selected climate models. Previous studies demonstrated that different models and different realizations in the same model may show quite different historical temperature evolution [68] There are 19 general circulation models (GCMs) in WorldClim, in these studies, we selected the CCSM4 model because it was widely adopted to simulate future climate change projection [69,70]. However, the comparative analysis of climate model performance in Qilian Mountains is needed in further research, which could provide the criterion for selecting models.…”
Section: Discussionmentioning
confidence: 99%
“…The difference may be attributed to different selected climate models. Previous studies demonstrated that different models and different realizations in the same model may show quite different historical temperature evolution [68] There are 19 general circulation models (GCMs) in WorldClim, in these studies, we selected the CCSM4 model because it was widely adopted to simulate future climate change projection [69,70]. However, the comparative analysis of climate model performance in Qilian Mountains is needed in further research, which could provide the criterion for selecting models.…”
Section: Discussionmentioning
confidence: 99%
“…Besides human pressure, the distribution of species also depends largely on climatic conditions, suggesting that climate change will affect the future availability of suitable habitat and hence species distributions [ 25 , 26 , 27 , 28 , 29 ]. As a result of climate change, suitable habitats may become increasingly fragmented or disappear altogether, causing further changes in biodiversity [ 30 , 31 ]. Climate change may shrink and/or shift species’ ranges, thereby increasing their vulnerability to external disturbances [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…One SDM, the MaxEnt algorithm, has proven powerful when modeling rare species with narrow ranges and scarce presence-only occurrence data [54,55]. This model is widely used in endangered species protection, protected area planning, invasive species control, and climate change impacts on the distribution of biological areas [7,16,26,27,29,56,57]. Therefore, we used MaxEnt (version 3.3.3k) in this study to model environmental suitability for giant pandas under RCP 4.5 in the year 2050.…”
Section: Methodsmentioning
confidence: 99%
“…However, most efforts are at medium or large scales. e.g., the studies have focused on the whole distribution range [24,25] or on mountain ranges, such as the Qinling Mountains [26][27][28], the Minshan Mountains [16,29] and the Daxiangling Mountains [30]. This is problematic because the results are difficult to translate into viable decisions.…”
Section: Introductionmentioning
confidence: 99%